"It's Always with You, that You're Different": Undocumented Students and Social Exclusion. Issue 2 (2nd April 2016) - Williams, Jean Calterone
ABSTRACT: This study focuses on undocumented college students who overcame significant barriers to apply to and attend universities, and once on campus, were forced to conceal their immigration status from staff and peers, struggling to pay tuition without assistance from scholarships or federal loans. The concept of social exclusion is used to understand and explore the barriers to their access to higher education and experiences while in college, relationships to community and governing institutions, and struggles with poverty and discrimination. The Obama Administration's Deferred Action for Childhood Arrivals initiative provides the first real possibility to more fully pursue their educational and employment aspirations and allows students to live without fear of deportation and social stigma, if only temporarily.